Maintaining Fan Loyalty in the Music Industry through a Cyber Marketing Strategy - Muchlis Abbas; Ibrahim Ibrahim; Taufik Thahir; Suriyanti Mangkona; Masyadi Masyadi; Kasnaeny Karim (Universitas Dharma Wacana, 2022)
This study aimed to examine the effect of marketing methods on fan loyalty towards Gigi Band. The research hypothesis was fully accepted at a probability level of 95%, indicating that marketing methods have a positive and significant effect on fan loyalty. The study also found that Gigi Band's management marketing strategy is very effective in maintaining its work and retaining its fans. The recommendations for future research include exploring additional variables that may influence fan loyalty beyond marketing methods. Additionally, the study suggests that Gigi Band should continue to hold concerts and expand its songwriting segment to increase its recognition among a wider audience. Overall, this research provides valuable insights into the impact of marketing on fan loyalty in the music industry.